Characteristics of Mechanical Strength and Flexibility of Shallots Leaf - Panjaitan, Lidia Kristina; Hermawan, Wawan; Supriyanto, Supriyanto; Triharjanto, Robertus Heru; Bahri, Sayr (PERTETA, 2024)
When operating drone sprayer, such as to distribute pesticides, downwash is the major cause of damage on the plants. Therefore, understanding the mechanical properties of plants are important to be able select the proper drone to use. In this research, characteristics of leaf strength and flexibility of two types of shallots were investigated, namely the Batu Ijo and Birma varieties. Research on the characteristics of the strength and flexibility of shallots was carried out from the 3rd to the 8th week for the Batu Ijo and 9 varieties of Birma, 100 samples each week. The strength of the leaf was measured by pulling the leaf until it breaks by attaching a thread to the base of the leaf which is pulled by a force gauge device. Then to measure its flexibility by pulling the top of the leaf with the thread that is pulled until it touches the ground surface. From this research, data on the strength characteristics of the leaves of the Birma variety 29 N that is much stronger than the Batu Ijo variety 8.9 N got obtained. Meanwhile, for the flexural characteristics, the Batu Ijo variety was 5 N with pressure P 0,113 N/cm2 more flexible than the Birma variety 3.3 N with pressure P 0,087 N/cm2. The minimum bending strength of the leaves for the two varieties F is almost the same, where for the Batu Ijo variety F 0.044 N with P 0.005 N/cm2 and for Birma varety F 0.041 N with pressure P 0.009 N/cm2. Based on the characteristics of this minimum bending, it becomes the basis for optimizing the design of the drone sprayer blade.